Epaisseur de la couverture morte sur des coupures de combustible arborées entretenues par le pâturage - Rigolot E.; Etienne M. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
Litter is a dead fine fuel layer composed of loose debris of dead sticks, branches, twigs, and recently fallen leaves or needles, which contributes to wildfire spreading. Natural processes, and artificial interventions for fuel-break maintenance are analysed to identify factors which accelerate litter decomposition and others which contribute to fine fuel build-up. The presence of trees and their density contribute to litter accumulation, but species and corresponding phenology shade this effect. Among fuel reduction techniques, roller chopping and herbicides application create new litter, where as prescribed burning and uprooting reduce litter depth. Grazing reduces litter cover more progressively. Fertilisation accelerates litter decomposition, but needs to be followed by intense grazing, otherwise a dead dry herbaceous layer may spread out.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)